Molecular Identification, Systematics, and Population Structure of Prokaryotes - Stackebrandt, Erko.; Stackebrandt, Erko. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Systematic biology has a far wider application than merely the provision of a reliable classification scheme for new strains. With the framework of the hierarchic system stabilizing, genomes, noncoding regions, and genes and their products can now be evaluated in an evolutionary context. This book summarizes recent developments in the molecular characterization of cultured and as-yet uncultured prokaryotes, emphasizing the strengths and weaknesses of individual approaches. The chapters of the book are compiled to stimulate students to enter the field of bacterial diversity, presenting a broad spectrum of fascinating multifaceted disciplines that illuminate the paths to ecosystem functioning, communication within communities, symbiosis, life in extreme environments, astrobiology, and more.